Program Bersih Lingkungan untuk Membangun Budaya Ekopeduli di Kalangan Mahasiswa - Rio Saputra; Muhammad Choirun Ni’am; Rommy Hardyansah; Didit Darmawan; Agung Satryo Wibowo (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The issue of environmental cleanliness is still a serious concern, especially considering the fact that the culture of environmental care among students and globally is still relatively low. It is unfortunate, even though students actually have knowledge about the importance of preserving nature, but in their daily practice it still seems less than optimal. To overcome this problem, this article aims to analyze the implementation of the environmental cleanup program as an effort to build an eco-care culture, especially among students through the Asset Based Community Development (ABCD) approach. This method was chosen because it is participatory by emphasizing the mapping of internal campus assets, such as optimizing existing student potential and then developing it through field observation, documentation, and participatory reflection. The program implemented includes environmental cleaning activities and greening the campus area as well as collaboration with all elements of society as a form of service to the surrounding community. The results of this program show an increase in student participation in environmental cleanup actions, marked by more consistent involvement in routine activities and increased student initiatives in maintaining the cleanliness of the campus area. Observations and reflections indicate a shift in student attitudes, from simply understanding the concept of environmental awareness to more responsible, pro-environmental behavior. This program also strengthens collective awareness that environmental cleanliness is a shared responsibility. These findings emphasize that fostering ecological practices, collaboration among students, and institutional support play a crucial role in fostering a sustainable culture of environmental awareness. This article also recommends developing similar, more participatory, long-term programs that strengthen students' role as agents of change on environmental issues.